Analisis Analisis Kelayakan finansial Perkebunan Kelapa Sawit PTPN IV, Kebun Melati, Kecamatan Pegajahan dan Perbaungan, Kabupaten Serdang Bedagai. - Anastasya, Vinye; -, Saprida (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2024)
This research discusses the Financial Feasibility of Oil Palm Plantations. Financial Feasibility is a tool used to analyze a business / project to determine whether or not a company is feasible in running its business, by examining the possible benefits of an investment / business. This research was conducted at PTPN IV oil palm plantation, Melati Plantation, Pegajahan and Perbaungan Districts, Serdang Bedagai Regency, North Sumatra Province. The research was conducted in June 2024, and the determination of the location was carried out intentionally (purposive) with the consideration that this area is one of the areas that have many oil palm plantations. In this study, researchers used two data, namely primary data and secondary data, where primary data was obtained through a direct interview process by asking questions that had been made, then the relevant Plantation would provide a verbal response or written response represented by the Plantation Manager, This research uses a type of Quantitative research, which analyzes data by calculating data (in the form of numbers) obtained as it is (Real Price). This research uses a financial feasibility analysis method consisting of npv, net b/c, irr, pbp. From the results of the research conducted, it can be concluded that the financial feasibility during the economic period of Oil Palm obtained, namely, NPV of Rp. 153,626,694,000, - Net B / C of 2.64, IRR of 21.03% and Payback Period of 4 years 5 months (starting from the year 2024) which is smaller than the economic period of growing oil palm in oil palm plantations in PTPN IV, Melati Plantation, Pegajahan and Perbaungan Districts, Serdang Regency, then based on the results of the analysis of the financial feasibility of this plantation is feasible to cultivate.